Interruption in Turn Taking Irregularities at Speaking for Conversation Class - Ani, Ikke Lusi; Damayanti, Indah; Sabarudin, Syafrizal (UNIB Press, 2024)
This research is aimed at finding types of interruption in turn taking irregularities at Speaking for Conversation Class and dominant type of interruption in turn taking irregularities at Speaking for Conversation Class. This research employed descriptive quantitative research. The subjects of this research were 2nd semester students of class A and C. The total subject was 80 students. This research used simple statistical (percentage) to analyze the data. The interruption in turn taking irregularities at Speaking for Conversation Class were classified using an instrument following Zimmerman & West theory and classified by Murata theory. The first finding showed seven types of interruption in turn taking irregularities at Speaking for Conversation Class, namely agreement, clarification, assistance, disagreement, floor taking, topic change, and tangelization. Meanwhile, the dominant type of interruption in turn taking irregularities was clarification types. These, the students didn’t like being interrupted in Speaking for Conversation Class either positive interruptions or negative interruptions. In conclusion, there were two types of interruption namely, cooperative and intrusive interruption. The cooperative interruption consists of agreement, clarification, and assistance. Then, the intrusive interruption consists of disagreement, floor taking, topic change, and tangelization. Than the dominant type of interruption was clarification types. It was suggested furthere researchers to used observation or recording instrument. More importantly, for furthere researchers also pay attention to the context and conditions of students.